Transforming Worker–Client Identities: From Shelters to Housing First - Löfstrand, Cecilia Hansen (Social Inclusion, 2021)
The Housing First (HF) approach to counteracting homelessness, stemming from the USA, is advocated as a blueprint for homelessness policy change in Europe, including the Nordic countries. In contrast to traditional homelessness policies based on shelters as the first step towards ending homelessness, the HF policy discourse regards access to one’s own housing as a basic human right that should not be conditional upon good or acceptable behaviour. Building on ethnographic research in a Swedish HF unit striving to implement the HF approach ‘by the book,’ which includes both focus group interviews with workers and observations of worker-client interactions during home visits, we show how the new HF policy challenges both workers and clients, who used to encounter each other in shelters but now meet in clients’ own homes, transforming their identities. We demonstrate how workers account for transformations in worker-client identities by referring to how they and their clients used to think, talk and act, thus contrasting their new identities with their former selves. Moreover, in their efforts to accomplish their actual work tasks within the framework of the new HF policy discourse in the homes of formerly homeless clients, we show how workers struggle with their identities when they encounter clients in practice. In their accounts of policy change, the workers embraced their new identities with pleasure, but in practice, they were hesitant when dealing with issues of concern, such as their clients’ use of tobacco, alcohol and drugs. In sum, it becomes complicated in practice.